Pengaruh Perencanaan Pajak (Tax Planning), Penghindaran Pajak (Tax Avoidance), Profitabilitas dan Kebijakan Dividen Terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Subsektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Nabila Zulfiandra Dewi; Ingra Sovita (GLOBAL SCIENTS PUBLISHER, 2025)
Firm value refers to investors’ perception of a company’s performance and prospects, as reflected in its stock price. It serves as an important indicator in assessing management's success in enhancing shareholder wealth. In this study, firm value is measured using the Price to Book Value (PBV), which indicates how much the market values a company compared to its book value. The higher the PBV, the higher the firm value, reflecting the market’s expectations for the company’s future performance and growth. This study aims to examine the effect of tax planning, tax avoidance, profitability, and dividend policy on firm value in telecommunication subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research adopts a quantitative approach using purposive sampling. Out of 23 companies in the telecommunication subsector used as the population, 115 observational data points were obtained, but only 85 met the criteria after filtering. The analytical tool used in this research is SPSS 21. The research results indicate that the tax planning variable (ETR) has a t-value of 2.402 > t-table 1.984 with a significance value of 0.018 < 0.050, indicating a positive and significant effect on firm value. The tax avoidance variable (CETR) has a t-value of -2.117 < t-table 1.984 and a significance value of 0.037 < 0.050, indicating that it does not significantly affect firm value. The profitability variable (ROA) shows a t-value of 2.222 > 1.984 and a significance value of 0.029 < 0.050, indicating a positive and significant influence on firm value. Meanwhile, the dividend policy variable (DPR) has a t-value of -1.672 < t-table 1.984 and a significance value of 0.098 > 0.050, indicating no significant effect on firm value. The results of the simultaneous test show that all four variables collectively have a significant effect on firm value, with an F-value of 5.174 > F-table 2.300 and a significance value of 0.001 < 0.050.